The Spiritual Aspect in Post-Amputation Clients - Nusawakan, Arwyn Weynand; Ranimpi, Yulius Y.; Kawonal, Johanna R. (ANIMA Indonesian Psychological Journal, 2012)
One of the conditions that cause various changes in individuals is amputation, which demands individuals to adapt to their new condition physically, psychologically, socially, and spiritually. The goal of this qualitative study was to reveal the spiritual aspects of post-amputation clients, using an in-depth interview and observation on three participants who were amputees. The data were analyzed using narrative analysis. Results showed that the participants considered their lives to be meaningful and be better in the future. They were self-confident and able to continue being productive even after the amputation. Their relationships with others were reflected in their daily lives, sharing their love with their closed ones. Their relationship with God was expressed through prayers and devotion in their daily lives. It can be concluded that the amputees showed the spiritual dimensions in themselves through their life meanings and their relationship between themselves, other people, God, and their hopes. Salah satu keadaan yang mengakibatkan terjadinya berbagai perubahan bagi individu adalah ketika anggota tubuhnya harus diamputasi sehingga individu harus mampu menyesuaikan diri dengan keadaannya barunya secara fisik, psikis, sosial, dan spiritual. Tujuan penelitian ini adalah menggambarkan aspek spiritual klien pascaamputasi.Penelitian kualitatif ini menggunakan teknik pengumpulan data wawancara mendalam dan observasi terhadap tiga partisipan yang telah diamputasi. Data dianalisis menggunakan analisis naratif. Hasil menunjukkan bahwa para partisipan memaknai hidup mereka dan memiliki harapan untuk menjadi lebih baik. Mereka memiliki sikap percaya pada diri sendiri dan merasa mampu berkarya meskipun telah diamputasi. Hubungan dengan orang lain tercermin dalam keseharian mereka membagi kasih dengan orang-orang terdekat. Hubungan dengan Tuhan diekspresikan melalui doa dan pengabdian dalam kehidupan sesehari. Dari penelitian ini disimpulkan bahwa para partisipan menunjukkan dimensi spiritualitas dalam diri mereka melalui makna hidup, hubungan antara diri sendiri, orang lain dan Tuhan serta berpengharapan.